KH Abdullah Syafi'i And The Heritage Of Betawi Islamic Boarding Schools: Modernization, Tradition, And Da'wah (1910–1985) - Muttaqin, Mohammad Izdiyan; Machmudi, Yon; Suyurno, S. Salahudin; Fajarini, Ulfah (Universitas Islam Indonesia, 2025)
KH. Abdullah Syafi'i (1910–1985) was a central Betawi scholar whose influence on Islamic education and urban da'wah in Jakarta remains understudied, particularly in relation to how his institutions navigated the intersection of pesantren traditions and educational modernization. Previous scholarship has largely focused on his biography or community activism, leaving a gap in explaining the structural transformation of Betawi-based Islamic schools and their contribution to the development of urban pesantren in Indonesia. This study addresses that gap by analyzingAbdullah Syafi'i’s educational initiatives, socio-religious leadership, and da'wah strategies within the broader evolution of modern Indonesian Islamic education. Employing a qualitative historical-sociological approach, the study draws on archival documents, institutional records, and selective interviews to trace the development of the As-Syafi'iyah educational network. The findings reveal that Abdullah Syafi'i introduced an integrated religious–general curriculum, strengthened mass da'wah through organized majelis taklim, utilized radio as a pioneering medium for Islamic outreach, and established orphan-based boarding schools as a model of urban social empowerment. The study argues that Abdullah Syafi'i represents a distinctive model of urban ulama who simultaneously preserved tradition and advanced modernization. His contributions expand the scholarly understanding of Indonesian Islamic education, offering an urban-based perspective on pesantren reform that challenges dominant rural and Java-centric frameworks.